2023
DOI: 10.3389/fpubh.2023.1150563
|View full text |Cite
|
Sign up to set email alerts
|

Predictive importance of the visceral adiposity index and atherogenic index of plasma of all-cause and cardiovascular disease mortality in middle-aged and elderly Lithuanian population

Abstract: BackgroundTwo indices: visceral adiposity index (VAI) and atherogenic index of plasma (AIP) during several recent years were implemented into epidemiological studies for predicting of cardiovascular diseases (CVD) and mortality risk. Our study aimed to evaluate the association of VAI and AIP with the risk of all-cause and CVD mortality among the Lithuanian urban population aged 45–72 years.MethodsIn the baseline survey (2006–2008), 7,115 men and women 45–72 years of age were examined within the framework of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…We showed that men had higher levels of AIP than women. Such sex differences in AIP values were revealed in similar literature 66,67 . However, other studies reported no significant association between AIP and hypertension incidence 68,69 .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…We showed that men had higher levels of AIP than women. Such sex differences in AIP values were revealed in similar literature 66,67 . However, other studies reported no significant association between AIP and hypertension incidence 68,69 .…”
Section: Discussionsupporting
confidence: 63%
“…Such sex differences in AIP values were revealed in similar literature. 66 , 67 However, other studies reported no significant association between AIP and hypertension incidence. 68 , 69 We recommend conducting further studies in larger populations to find the association between AIP and hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…Relationship of AIP and CVD-specific mortality was also found in patients aged ≥ 60 years old. A study on predictive performance of AIP of all-cause mortality and CVD-specific mortality in middle-aged and elderly Lithuanian population showed that the risk of CVD mortality significantly increased in males with the highest AIP quintile compared with that for the lowest quintile [ 27 ]. In females, all-cause mortality was significantly higher for the 4th quintile of AIP as compared with the 1st quintile [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study on predictive performance of AIP of all-cause mortality and CVD-specific mortality in middle-aged and elderly Lithuanian population showed that the risk of CVD mortality significantly increased in males with the highest AIP quintile compared with that for the lowest quintile [ 27 ]. In females, all-cause mortality was significantly higher for the 4th quintile of AIP as compared with the 1st quintile [ 27 ]. Płaczkowska et al [ 28 ] found that different lipid parameters and AIP are associated with a high concentration of small dense LDL depending on the age group.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the VAI and BAI are crucial tools for evaluating cardiometabolic risk, particularly in the context of adipose tissue dysfunction and its role in the development of CVDs. The application of both indices in clinical practice may contribute to a better understanding and management of cardiometabolic risk, particularly in post-MI patients [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%